Evaluasi Program Pembinaan Prestasi Bolavoli Putri Sekolah Menengah Atas Negeri 1 Kota Gorontalo - Mokodenseho, Muhammad Rezky; Pramono, Harry; Irawan, Fajar Awang (Gelanggang Olahraga: Jurnal Pendidikan Jasmani dan Olahraga (JPJO), 2024)
This research aims to describe the evaluation of the Women's Volleyball Sports Performance Development Program for State High School 1 Gotontalo City. This research uses a stake model evaluation (Countenance Model): antecedents/context, transactions/process, and outcomes/results. This research uses a qualitative approach. This research design is descriptive and uses qualitative research methods. The results of the research in the discussion show that the results of the Evaluation of the Gorontalo City 1 State High School Girls' Volleyball Development Program are in terms of the antecedent (context) of the Gorontalo 1 State High School volleyball development program, which includes the absence of a clear vision and mission, the lack of coordination between educational level coaches. Previously, the long-term development of young athletes had not been running at all, and facilities and infrastructure needed to be by national standards. The conclusion is that the volleyball performance development program at SMA Negeri 1 Gorontalo is not optimal in terms of management, fund management, training programs, and support from the government. The welfare of administrators, coaches, and athletes is still minimal. Keywords: volleyball, evaluation, learning program